Psychological Aspects of Evaluation of Personnel in the System of Public Service - Malimon, Lyudmila Ya. (Psychological Prospects Journal, 2017)
The article is dedicated to the study of psychological aspects of estimation of personnel in the system of public service. It was determined the main reasons of inefficiency of such estimation: formality and subjectivity, lack of feedback, inconsistency of employee’s self-estimation and experts’ estimation, inadequate perception by civil servants of the essence of evaluation. The specifity of professional activity in the system of public administration: publicity, social orientation, focus on the needs of citizens has been underlined. It was mentioned that “estimation” is the main element of the notion of “effectiveness of public administration”, as it reflects the level of society’s development and the level of functioning of the public service. Attention was paid on socio-psychological essence of estimation, insufficient elaboration and definition of requirements (social norms) to a personality and activity of public servants, necessity of development of adequate methods and estimation procedures. The results of empirical study in the course of which it was revealed professionally important qualities of public servants have been generalized, the criteria and indices of estimation of the level of their professionalism have been singled out and grounded, and the effectiveness of different diagnostic techniques of estimation of personnel in the system of public service has been compared. With the help of direct assessment methods and forced choice were defined the level of necessity and the level of formation of professionally important qualities among public servants which found their reflection in evaluation letter of estimation of personnel in the system of public service. The criteria of analysis of professional activity of public servants (professionalism; labor and executive discipline; personal (professionally important) qualities; interaction with management, colleagues, customers; professional motivation; need in training; the volume of performed work) have been singled out, qualitative and quantitative indices for analysis of each criteria have been proposed. It was carried out the procedure of expert estimation of importance of the singled out criteria and their accordance with official duties of an employee. It was grounded the importance of consolidation of these methods for obtaining more objective and full information, minimizing the effect of social desirability in estimation of personnel in the system of public service.Key words: personnel, estimation, public service, professionally important qualities, method of direct choice, method of forced choice, evaluation letter, expert estimation.